Relationship between loss of pigmentation and deletion of the chromosomal iron-regulated irp2 gene in Yersinia pestis: evidence for separate but related events. - Iteman, I (1993)
The irp2 gene, coding for a 190-kDa iron-regulated protein (HMWP2), and the hemin storage locus (hms), which determines Yersinia pestis pigmentation, are each located on a large chromosomal fragment which carries virulence genes and deletes spontaneously. To determine whether the two loci are located on one unstable fragment or on two different excisable DNA segments, the pigmentation status and the presence of irp2 in 43 strains of Y. pestis isolated in various parts of the world were examined. Three different types were observed: Pgm+ Irp2+ (39.5%), Pgm- Irp2- (44.2%), and Pgm- Irp2+ (16.3%). No Pgm+ Irp2- strain was found. These three types were also recovered in vitro from the parental strain Saigon 55-12-39 (Pgm+ Irp2+), but again, no Pgm+ Irp2- colony was observed. Pgm- Irp2- derivatives were obtained from a single Pgm- Irp2+ colony, indicating sequential loss of the two traits. The fact that the genomic SpeI restriction patterns obtained by pulsed-field gel electrophoresis were specific for each of the three variants suggested that distinct large-scale chromosomal rearrangements had occurred in the Pgm- Irp2+ and Pgm- Irp2- derivatives. The virulence of Pgm- Irp2+ bacteria in mice was ca. 10(7)-fold lower than that of the Pgm+ Irp2+ strains injected subcutaneously but was not significantly decreased when injected intravenously. In contrast, the Pgm- Irp2- microorganisms were markedly less pathogenic (10(6)-fold) than the Pgm+ Irp2+ strains injected intravenously and were 100 times less virulent than the Pgm- Irp2+ strains injected subcutaneously.